Evaluation of pushout bond strength of surface-treated glass fiber posts using universal adhesives with and without Silanization: an in vitro study - Chundi, Sai Vinitha; Praharshini, Yadapalli; Sampathi, Naga Lakshmi Reddy; Moosani, Gopi Krishna; Reddy, E Sujayeendranath; Meenakshi, Meher (International Journal of Dental Materials, 2024)
Background: Endodontically treated teeth that lack coronal tooth structure may require the placement of a post to provide adequate retention of a core foundation followed by a crown. Glass fiber posts have become one of the most popular because of the similar modulus of elasticity to dentin. Aim: To evaluate the push-out bond strength of surface-treated glass fiber posts to intraradicular dentin using universal adhesives with and without silanization. Materials and methods: Thirty single-rooted teeth were prepared up to the working length in a step-back technique and obturated. Post space was prepared to the length of 10 mm. Based on silanization specimens were divided into two groups of 15 each. Clearfil Tri-S bond universal was used as a bonding agent. The two groups including, Group 1 (without Silanization) (CTSBU): post-treatment - only 9%HF, and Group 2 (With Silanization) (CTSBU+S): post-treatment - 9%HF followed by silane. RelyxU200 was used to lute the posts, and the samples were divided into three parts (cervical, middle, and apical) and subjected to push-out bond strength analysis. Overall comparisons were done by analysis of variance (ANOVA), and pairwise comparisons were done by student t-test. The level of significance was set at p < 0.05 for all tests. Results: In all the root regions, group 2 (CTSBU+S) showed the highest pushout bond strength with statistical significance (p<0.05) when compared to other groups. In all the groups, the cervical region showed the highest bond strength when compared to the middle and apical regions which were significant (p<0.05). Conclusion: It can be concluded that the Silanization of the glass fiber posts showed to improve the bond strength and the cervical region has better bond strength among the three regions of the post.